Positive electrode material, positive electrode plate and secondary battery

By designing uneven element M distribution and appropriate amount of sulfur atom doping in the positive electrode material particles, the problem of prone to cracks in the long-term cycle is solved, and higher cycle stability and rate performance are achieved.

CN119764414APending Publication Date: 2025-04-04SHENZHEN CITY BATTERY NANOMETER TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411981549.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing positive electrode materials are prone to cracks during long-term cyclic charging and discharge, which affects their cyclic stability.

Method used

A positive electrode material is used, and the elements M of its particles (such as Na, K, Mg, Ca, Sr or Ba) are distributed unevenly on the slit surface, the concentration of element M in the surface area is higher, and the concentration of element M in the central area is lower, forming a compressive stress from the surface layer to the center, inhibiting lattice expansion. At the same time, the ratio of the total mass content of sulfur element to the mass content of sulfur element in free sulfate is controlled within 70%, and some sulfur atoms are doped into the crystal lattice, improving the migration rate and structural stability of lithium ions.

Benefits of technology

By forming compressive stress, the stability of particles is improved, the cycle life of the cathode material is extended, and its magnification and structural stability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764414A_ABST
    Figure CN119764414A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material, a positive electrode plate and a secondary battery, the positive electrode material comprises an element M, and the element M is selected from at least one of Na, K, Mg, Ca, Sr or Ba; the positive electrode material comprises a plurality of particles, the tangent plane of each particle comprises a central region and a surface region, the tangent plane of each particle is tested through an energy disperse spectroscopy, the average concentration of an element M in the central region is X1, the average concentration of the element M in the surface region is X2, and X1 and X2 meet the condition that X2 / X1 is larger than or equal to 1.2 and smaller than or equal to 20; the total mass content of the sulfur element in the positive electrode material is A1, the mass content of the sulfur element in the free sulfate radical in the positive electrode material is A2, and (A2 / A1)% is less than or equal to 70%. The positive electrode material provided by the invention is stable in structure and low in direct-current resistance, and is beneficial to improving the cycle performance and long-term electrochemical performance of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery positive electrode materials, and in particular to a positive electrode material, a positive electrode sheet and a secondary battery. Background Art

[0002] Positive electrode materials are one of the core materials of current lithium batteries. The development of positive electrode materials is relatively slow compared to the development of large-capacity negative electrode materials (about 800-1000mAh / g). How to increase the capacity of positive electrode materials is the main research direction of positive electrode materials. However, as the capacity of positive electrode materials increases, positive electrode materials will produce cracks during long-term cycle charge and discharge, affecting the cycle stability of positive electrode materials. Summary of the invention

[0003] In view of this, in order to solve at least one of the above defects, the present application provides a positive electrode material to improve the cycle stability of the positive electrode material.

[0004] In addition, the present application also provides a positive electrode sheet and a secondary battery using the positive electrode material.

[0005] The present application provides a positive electrode material, the positive electrode material includes an element M, the element M is selected from at least one of Na, K, Mg, Ca, Sr or Ba; the positive electrode material includes a plurality of particles, the cross section of the particle includes a central region and a surface region, the cross section of the particle is tested by an energy spectrometer, the average concentration of the element M in the central region is X1, the average concentration of the element M in the surface region is X2, X1 and X2 satisfy: 1.2≤X2 / X1≤20; the total mass content of sulfur in the positive electrode material is A1, the mass content of sulfur in free sulfate in the positive electrode material is A2, A1 and A2 satisfy: (A2 / A1)%≤70%

[0006] In some embodiments, 30%≤(A2 / A1)%≤50%.

[0007] In some embodiments, the molar content of the element M is 50 ppm to 1000 ppm based on the total molar amount of the positive electrode material.

[0008] In some embodiments, based on the total molar amount of the positive electrode material, the molar content of the element S is 100 ppm to 3000 ppm.

[0009] In some embodiments, the positive electrode material is a single crystal material, and the particles include primary particles, and the average particle size of the primary particles is 1 μm to 5 μm.

[0010] In some embodiments, during the first cycle of charge and discharge of the positive electrode material, the degree of structural recovery δ of the positive electrode material satisfies: 99.70%≤δ≤100.00%, wherein δ=θ1 / θ2*100%, θ1 is the diffraction angle of the X-ray diffraction (003) peak of the positive electrode material at the beginning of the first cycle of charging, and θ2 is the diffraction angle of the X-ray diffraction (003) peak of the positive electrode material at the end of the first cycle of discharge.

[0011] In some embodiments, the general formula of the positive electrode material is: Li x Ni a Co b Q c M d O2, wherein 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.35, a+b+c=1, 0.00005<d≤0.001, and the Q element includes at least one of Mn and Al.

[0012] In some embodiments, the positive electrode material further contains element N, and element N is selected from one or more of Zr, Ti, Al, W, Ce or Y; based on the total molar amount of the positive electrode material, the molar content of element N accounts for e, 0<e≤0.05.

[0013] In some embodiments, the volume distribution particle size D50 of the positive electrode material is 2.5 μm to 5.0 μm.

[0014] In some embodiments, the specific surface area of ​​the positive electrode material is 0.5 m 2 / g to 1.2m 2 / g.

[0015] In some embodiments, the volume proportion of particles with a particle size of less than 1 μm in the positive electrode material under a pressure of 6 t is less than 4%.

[0016] The present application also provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a single crystal positive electrode material.

[0017] The present application also provides a secondary battery, including a shell, an electrode assembly, and an electrolyte or an electrolyte, the electrode assembly and the electrolyte or the electrolyte are both located in the shell, the electrode assembly includes a separator and a negative electrode plate, the electrode assembly also includes a positive electrode plate, and the separator is arranged between the positive electrode plate and the negative electrode plate.

[0018] In the present application, the positive electrode material contains element M, and the element M is unevenly distributed in the particles. The concentration of element M satisfies the above relationship at the surface and center of the particles, so that the content of element M near the surface area of ​​the particles is relatively high. The M element increases the unit cell volume of the surface area of ​​the particles, while the content of element M near the center area of ​​the particles is relatively low, so that the unit cell volume in the center area of ​​the particles is relatively small, thereby forming a compressive stress from the surface area to the center area of ​​the particles. The compressive stress can inhibit the lattice expansion during the charge and discharge process, improve the stability of the particles, and thereby improve the gas production performance and long-term cycle performance. At the same time, in the present application, the total mass content of sulfur in the positive electrode material is A1, the mass content of sulfur in the free sulfate ions in the positive electrode material is A2, and the ratio of A2 to A1 is ≤70%. A1 and A2 can characterize the enrichment degree of sulfur on the surface of the positive electrode material. When the ratio of A2 to A1 in the positive electrode material is ≤70%, it indicates that part of the sulfur atoms are doped into the lattice of the positive electrode material. The appropriate amount of sulfur atom doping can increase the migration rate of lithium ions, inhibit heterogeneous reactions, reduce the lattice rotation of the positive electrode material, and improve the rate and structural stability of the positive electrode material.

[0019] Main component symbols

[0020] The electrode assembly 100 includes a positive electrode sheet 101 , a negative electrode sheet 102 and a separator 103 . BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during charging.

[0022] Figure 2 It is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during discharge.

[0023] Figure 3 Schematic diagram of the structure of the concentration distribution of element M in this application. DETAILED DESCRIPTION

[0024] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0025] The present application provides a secondary battery, comprising a housing, an electrode assembly and an electrolyte (or electrolyte). The electrode assembly and the electrolyte are both located in the housing.

[0026] The outer shell can be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), for example, a soft-pack battery. In other embodiments, it can also be a steel shell battery, an aluminum shell battery, etc.

[0027] See also Figure 1 and Figure 2 The electrode assembly 100 includes a positive electrode sheet 101, a negative electrode sheet 102 and a separator 103, wherein the separator 103 is disposed between the positive electrode sheet 101 and the negative electrode sheet 102. Figure 1 During discharge, active ions (such as lithium ions) are deintercalated from the lattice of the negative electrode material of the negative electrode plate 102, pass through the electrolyte through the separator 103, reach the positive electrode plate 101 and are embedded in the lattice of the positive electrode material (such as the lithiated intercalation compound), and generate electrons from the negative electrode plate 102 through the external circuit to the positive electrode plate 101. The reverse movement of the electrons forms an electric current that can be used by electrical appliances. When charging, please refer to Figure 2 , active ions (such as lithium ions) are deintercalated from the lattice of the positive electrode material (such as the lithiated intercalation compound) of the positive electrode plate 101, pass through the isolation membrane 103 through the electrolyte, reach the negative electrode plate 102 and are inserted into the lattice of the negative electrode material.

[0028] In some embodiments, the electrode assembly 100 may be a laminated structure, which is formed by alternately stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102. In other embodiments, the electrode assembly 100 may also be a wound structure, which is formed by stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102 in sequence and then winding them.

[0029] The present application also provides a positive electrode material, the positive electrode material includes an element M, and the element M is selected from at least one of Na, K, Mg, Ca, Sr or Ba; the positive electrode material includes a plurality of particles, the cross-section of the particle includes a central region and a surface region, and the cross-section of the particle is tested by an energy dispersive spectrometer (EDS), and the average concentration of the element M in the central region is X1, and the average concentration of the element M in the surface region is X2, and X1 and X2 satisfy: 1.2≤X2 / X1≤20; the total mass content of sulfur in the positive electrode material is A1, and the mass content of sulfur in free sulfate ions in the positive electrode material is A2, and A1 and A2 satisfy: (A2 / A1)%≤70%.

[0030] In the present application, the positive electrode material contains element M, and element M is selected from at least one of Na, K, Mg, Ca, Sr or Ba. The concentration of element M in the surface area and the central area of ​​the particle satisfies the above relationship, so that the content of element M near the surface area of ​​the particle is relatively high, and the M element increases the unit cell volume of the surface area of ​​the particle, while the content of element M near the central area of ​​the particle is relatively small, so that the unit cell volume in the central area of ​​the particle is relatively small, thereby forming a compressive stress of the particle from the surface area toward the central area. The compressive stress can inhibit the lattice expansion during the charge and discharge process, improve the stability of the particles, and thereby improve the long-term cycle performance of the positive electrode material. In addition, in combination with the fact that the ratio of A1 to A2 in the positive electrode material in the present application satisfies: (A2 / A1)%≤70%, A1 and A2 can characterize the degree of enrichment of sulfur element on the surface of the positive electrode material. When the ratio of A2 to A1 in the positive electrode material is ≤70%, it indicates that part of the sulfur atoms are doped into the crystal lattice of the positive electrode material. After the sulfur atoms are doped into the crystal lattice of the positive electrode material, they can replace the oxygen atoms in the layered structure of the positive electrode material, thereby increasing the migration rate of lithium ions, inhibiting heterogeneous reactions, reducing the lattice rotation of the positive electrode material, improving the structural stability of the positive electrode material, maintaining the compressive stress in the particles, further inhibiting the lattice expansion during the charge and discharge process, and improving the cycle stability of the positive electrode material.

[0031] It should be noted that in this application, Figure 3 As shown, in the cross-sectional view of the particle, the radius of the particle is L, the area from the center of the particle to the distance L / 2 from the center of the particle is the central area, and the area from the position L / 2 of the particle to the surface of the particle is the surface area.

[0032] When X2 / X1<1.2, the unit cell volume of the surface area of ​​the particle is evenly distributed with the unit cell volume of the center area, and it is difficult to form compressive stress from the surface area to the center area. When X2 / X1>20, too much element M will be enriched in the surface area of ​​the particle, occupying the lattice lithium site, affecting the transmission and diffusion of lithium ions at the interface, and reducing the rate performance of the secondary battery. When the value of (A2 / A1)% is greater than 70%, it indicates that most of the S in the positive electrode material is in the form of free SO4 2- The content of S doped into the bulk phase is small, which is not conducive to the migration of Li, resulting in a decrease in the capacity and rate performance of the positive electrode material.

[0033] In some embodiments, the ratio of X2 / X1 can be 1.2, 1.5, 2, 5, 7, 9, 10, 12, 14, 16, 18, 20, or any value in the range formed by any two of the above values. The value of the element (A2 / A1)% can be 20%, 30%, 40%, 50%, 60%, 70%, or any value in the range formed by any two of the above values.

[0034] In some embodiments, 30%≤(A2 / A1)%≤50%, and the positive electrode material meets this range, which is beneficial to further reduce the lattice rotation of the positive electrode material, improve the rate and structural stability of the positive electrode material, thereby improving the cycle performance of the positive electrode material and further reducing the DC resistance.

[0035] In some embodiments, based on the positive electrode material, the molar concentration of element M is 50ppm to 1000ppm. The concentration of element M is within the above-mentioned suitable range, which is conducive to making the particles contain suitable element M, and making element M maintain a suitable unit cell volume size, which is conducive to improving the cycle stability of the positive electrode material. If the molar concentration of element M is lower than 50ppm, the effect of doping element M is not obvious, which is not conducive to the formation of compressive stress; when the molar concentration of doping M element is too high, such as greater than 1000ppm, it is not conducive to the diffusion of Li, causing the positive electrode material impedance to increase. In some embodiments, the concentration of element M can be 50ppm, 80ppm, 100ppm, 150ppm, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm or any value within the range composed of any two of the above values. Preferably, based on the positive electrode material, the molar concentration of element M is 200ppm to 600ppm.

[0036] In some embodiments, based on the positive electrode material, the molar content of element S is 100ppm to 3000ppm. Suitable element S content is conducive to further improving the tolerance of the positive electrode material to lattice deformation and improving the stability of the positive electrode material. In some embodiments, the molar content of element S can be 100ppm, 200ppm, 300ppm, 400ppm, 500ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm or any value within the range of any two of the above values. Preferably, based on the mass of the positive electrode material, the total content of element S is 500ppm to 2000ppm.

[0037] In some embodiments, the positive electrode material is a single crystal material, and the positive electrode material includes a plurality of primary particles, and the average particle size of the primary particles is 1 μm to 5 μm. The particle size of the primary particles is within the above range, which is beneficial to maintaining a good specific capacity and low direct current resistance (DCR) of the positive electrode material, and is also beneficial to reducing the side reaction between the primary particles and the electrolyte, so that the positive electrode material maintains good cycle stability. In some embodiments, the average particle size of the primary particles can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or any value within the range composed of any two of the above values. When the average particle size of the primary particles is less than 1 μm, the side reaction between the material and the electrolyte is serious, and the risk of gas production during high-temperature storage is high; when the average particle size of the primary particles is greater than 5 μm, the diffusion path of Li ions is long and the rate performance is poor.

[0038] In the present application, the difference between single crystal positive electrode material and polycrystalline positive electrode material (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nanometer-scale primary particles. For single crystal positive electrode materials, the smallest particle is usually a single primary particle of micrometer scale. Generally speaking, in addition to the EBSD test method, it is also possible to determine whether the obtained positive electrode product is a single crystal material by characterization methods such as scanning electron microscopy (SEM). For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. It can be observed by EBSD that the color in the grains is the same, so as to judge that the orientation in the grains is the same, and the grains with the same orientation are single crystals. It should be specially noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. Crystallographically, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal cathode materials known in the art are actually more "single crystal morphology" cathode materials, which only show the size of large single crystal particles and are different from polycrystalline particles composed of many small primary particles.

[0039] It is understandable that a single crystal grain in the present application may be a single particle composed of a primary particle. The above-mentioned single crystal positive electrode material may also contain a small amount of "quasi-secondary particles" formed by the adhesion of several single particles. "Quasi-secondary particles" refer to particles formed by the adhesion of several single particles. Usually, the particle size of a single particle in the above-mentioned quasi-secondary particles is usually between 1 μm and 5 μm. In general, the particle size and roundness of the "quasi-secondary particles" are significantly different from those of conventional polycrystalline.

[0040] In some embodiments, during the first cycle of charge and discharge of the positive electrode material, the structural recovery degree δ of the positive electrode material satisfies: 99.70%≤δ≤100.00%, wherein δ=θ1 / θ2*100%, θ1 is the diffraction angle of the X-ray diffraction (003) peak of the positive electrode material at the beginning of the first cycle of charge, and θ2 is the diffraction angle of the X-ray diffraction (003) peak of the positive electrode material at the end of the first cycle of discharge. When the structural recovery degree δ of the positive electrode material is within the above-mentioned suitable range, the positive electrode material has good structural stability and capacity, and is also conducive to reducing the DC resistance of the positive electrode material. The structural recovery degree δ of the positive electrode material can be 99.7%, 99.8%, 99.9%, 100.0%, or any value within the range formed by any two of the above-mentioned values.

[0041] In some embodiments, the general formula of the positive electrode material is: Li x Ni a Co b Q c M d O2, wherein 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.35, a+b+c=1, 0.00005<d≤0.001, Q element includes at least one of Mn and Al, and element M is selected from at least one of Na, K, Mg, Ca, Sr or Ba. The positive electrode material contains nickel, cobalt and manganese elements. The ion radius of element M in the positive electrode material is relatively large. After entering the transition metal layer and occupying the site of Ni / Co / Mn elements, the M element with a large ion radius will expand the distance between the transition metal layers, thereby increasing the unit cell volume in this area, and combined with the different contents of element M in the central area and the surface area, a compressive stress of the particles from the surface area to the central area is formed, thereby improving the stability of the particles. At the same time, after some sulfur elements are doped into the crystal lattice, they can form O-TM-S chemical bonds. TM is a transition metal in the crystal lattice. This chemical bond has stronger bond energy, which can enhance the tolerance of the positive electrode material to lattice deformation, alleviate the generation of cracks inside the positive electrode material particles and irreversible phase changes, and improve the cycle stability of the positive electrode material.

[0042] In some embodiments, the positive electrode material contains element N, and element N is selected from one or more of Zr, Ti, Al, W, Ce or Y. Doping element N in the positive electrode material is beneficial to further reduce the direct current internal resistance (DCR) of the positive electrode material, stabilize the positive electrode material, and improve the ionic conductivity and cycle stability of the positive electrode material. Based on the total molar amount of the positive electrode material, the molar content of element N is e, 0<e≤0.05. The content of element N is within the above-mentioned suitable range, which is beneficial to further stabilize the structure of the positive electrode material and improve the cycle stability of the positive electrode material.

[0043] In some embodiments, the particle size D50 of the positive electrode material is 2.5 μm to 5.0 μm. The particle size distribution of the positive electrode material is within the above range, which is conducive to maintaining good discharge capacity and rate performance of the positive electrode material and improving the electrochemical performance of the positive electrode material. The particle size D50 of the positive electrode material can be 2.5 μm, 3 μm, 4 μm, 5 μm or any value within the range formed by any two of the above values.

[0044] In some embodiments, the specific surface area of ​​the positive electrode material is 0.5 m 2 / g to 1.2m 2 / g. It is beneficial to reduce the contact between the positive electrode material and the electrolyte, reduce the occurrence of side reactions, and make the positive electrode material have good discharge capacity and cycle performance. In some embodiments, the specific surface area of ​​the positive electrode material can be 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g, 1.2m 2 / g or any value within the range formed by any two of the above values.

[0045] In some embodiments, the volume proportion of particles of the positive electrode material with a particle size of less than 1 μm under a pressure of 6t is less than 4%. The volume proportion of particles of the positive electrode material with a particle size of less than 1 μm under a pressure of 6t can be 3.9%, 3.8%, 3.6%, 3.5%, 3.2%, 2.9%, 2.5%, 2% or 1.5%. The lower the number of particles below 1 μm under a pressure of 6t, the higher the compressive strength of the positive electrode material, and the positive electrode material particles are not easily crushed during the production process of the pole piece, thereby having better structural stability.

[0046] The present application also provides a method for preparing a positive electrode material, comprising the following steps:

[0047] S1. According to the molar ratio of Ni:Co:Mn / Al:M (0.5-0.95):(0-0.2):(0-0.35):(0.0005-0.001), nickel salt, cobalt salt, manganese salt and M salt are added into water, mixed evenly, and an appropriate amount of H2SO4 is added to make the molar content of S element be 100ppm-3000ppm; then, the mixture is stirred and ultrasonically for more than 1h to obtain a mixed solution, wherein the element M is selected from at least one of Na, K, Mg, Ca, Sr or Ba.

[0048] Among them, the Ni salt, Co salt, Mn salt, Al salt and M salt can be independently selected from at least one of chloride, nitrate, oxalate and acetate, preferably nitrate.

[0049] In some embodiments, based on the total molar content of metal Ni, Co, and Mn / Al as 100%, the amount of H2SO4 added is 0.015% to 0.3%. Specifically, the amount of H2SO4 added can be 0.015%, 0.03%, 0.05%, 0.08%, 0.1%, 0.12%, 0.15%, 0.2%, 0.25%, 0.3%, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0050] S2. The mixed solution is prepared into micronized droplets of 2 μm to 200 μm by ultrasonic atomization, and then enters the calcining furnace for thermal decomposition to prepare Ni / Co / Mn oxide precursor. In this step S2, the atomized droplets after ultrasonic atomization pass through three temperature zones of the calcining furnace in sequence.

[0051] The temperature of the first temperature zone is 300°C-500°C. Specifically, the temperature of the first temperature zone is 300°C, 350°C, 380°C, 400°C, 430°C, 450°C or 500°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here. The residence time in the first temperature zone is 30s-60s. The residence time in the first temperature zone is 30s, 35s, 40s, 45s, 50s, 55s or 60s, etc. Of course, it can also be other values ​​within the above range, which is not limited here. In the first temperature zone, the droplets are quickly dehydrated so that the droplets form dry materials.

[0052] The temperature of the second temperature zone is 1000℃-1200℃, and the temperature of the second temperature can be specifically 1000℃, 1050℃, 1100℃, 1150℃ or 1200℃, etc., and of course it can also be other values ​​within the above range, which is not limited here. The residence time in the second temperature zone is 2s~10s, and can be specifically 2s, 3s, 5s or 10s, etc., and of course it can also be other values ​​within the above range. The material (particles after dehydration after passing through the first temperature zone) stays in the second temperature zone for 2s~10s. Within this time range, the precursor particles can be prevented from growing too large, which will affect the reaction activity of the precursor. At the same time, the short high temperature can also promote the doping of element S into the precursor.

[0053] The pyrolysis temperature of the third temperature zone is 500°C-800°C, and the temperature of the third temperature zone can be 510°C, 520°C, 530°C, 550°C, 600°C, 650°C, 680°C, 700°C, 750°C or 800°C, etc., and of course it can also be other values ​​within the above range, which is not limited here. The material residence time in the third temperature zone is 2min-5min, and can be specifically 2min, 2.3min, 2,5min, 2.8min, 3min, 3.5min, 4min, 4,5min or 5min. Of course it can also be other values ​​within the above range, which is not limited here. In the third temperature zone, the metal salt of Ni / Co / Mn / M further decomposes to form an oxide precursor.

[0054] By controlling the content of element M in step S1 and the temperature and time of each temperature zone in the calcination in step S2, the content of element M in the positive electrode material X2 / X1 satisfies 1.2≤X2 / X1≤20. Then, by controlling the content of sulfuric acid added in step S1 and the calcination temperature and atmosphere in step S2, the ratio of A2 to A1 is ≤70%.

[0055] Specifically, in step S2, the oxygen volume concentration of the roasting furnace is lower than 21%. When the oxygen volume concentration is ≤21%, a non-oxygen-rich environment is easily formed in the roasting furnace. The oxygen volume concentration of the roasting furnace can be 21%, 20%, 19%, 18%, 17%, 16%, 15%, 13%, 11%, 9% or 5%. Under this condition, part of SO4 2- The medium energy decomposition forms S 2- Low-valent ions such as S can be removed, making it easier for element S to enter the crystal lattice inside the cathode material precursor, which is beneficial for the subsequent preparation of cathode materials doped with element S inside the grains to improve the migration rate of Li.

[0056] In step S2, the general formula of the precursor is Ni a Co b Q c M d O y , wherein 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.35, 0.00005<d≤0.001, a+b+c=1, 1≤y≤1.4, the Q element includes at least one of Mn and Al. The element M is selected from at least one of Na, K, Mg, Ca, Sr or Ba.

[0057] In step S2, the precursor can also be pulverized by airflow to control the particle size D50 of the precursor to be 2.5μm to 4.5μm, Dmax < 20μm, and the positive electrode material prepared by the precursor under this particle size has a dispersed morphology and a small amount of fine powder. D50 can specifically be 2.5μm, 3.0μm, 3.5μm, 4.0μm, 4.2μm or 4.5μm, etc., and of course it can also be other values ​​within the above range.

[0058] S3. Weigh a mixture of an oxide precursor and a lithium source in a certain molar ratio and perform sintering treatment to obtain a positive electrode material.

[0059] In step S3, the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate, lithium sulfate and lithium oxalate. Preferably, the lithium salt is lithium carbonate.

[0060] In step S3, the added amounts of the lithium source and the oxide precursor satisfy: the ratio of the molar amount of Li to the total molar amount of all metals in the oxide precursor is (0.98-1.1):1, specifically 0.98:1, 1.02:1, 1.05:1, 1.1:1, etc., and of course other values ​​within the above range may also be possible, which are not limited here.

[0061] In step S3, the mixing conditions of the mixture are: solid phase mixing at 10°C to 50°C for 0.3h to 3h.

[0062] In step S3, the temperature of the solid phase mixing can be 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C or 50°C, and the time of the solid phase mixing can be 0.3h, 0.4h, 0.5h, 0.6h, 0.8h, 1h, 1.5h, 1.8h, 2.5h or 3h, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0063] In step S3, the mixing equipment may be at least one of a ball mill, a three-dimensional mixer, a high-speed mixer and a VC mixer.

[0064] In step S3, an oxide containing element N (dopant) may be added to the lithium carbonate and the oxide precursor, and the mixture is evenly mixed and then sintered at high temperature for 20 hours in an oxygen atmosphere to obtain a positive electrode material.

[0065] In step S3, the sintering temperature is 750°C to 980°C. Specifically, the sintering temperature can be 750°C, 780°C, 800°C, 830°C, 850°C, 870°C, 900°C, 950°C or 980°C. Of course, it can also be other values ​​within the above range, which is not limited here.

[0066] In step S3, the sintering time is 4 hours to 16 hours. Specifically, the sintering time can be 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours or 16 hours. Of course, it can also be other values ​​within the above range, which is not limited here.

[0067] In step S3, the oxide containing element N may be at least one of ZrO2, Y2O3, WO3, Al2O3, CeO2, and TiO2.

[0068] In step S3, the molar ratio of the oxide precursor, the oxide containing element N (dopant) and the lithium source is 1:(0-0.05):(0.98-1.1). Specifically, it can be: 1:0.01:0.98, 1:0.02:0.99, 1:0.03:0.99 or 1:0.05:1.1. Of course, it can also be other values ​​within the above range, which is not limited here.

[0069] Negative electrode

[0070] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector.

[0071] The negative electrode current collector includes copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, a polymer substrate coated with a conductive metal, or any combination thereof.

[0072] In some embodiments, the negative electrode active material layer includes a negative electrode active material. The specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. In some embodiments, the negative electrode active material includes, but is not limited to: lithium metal, structured lithium metal, natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy or any combination thereof. The silicon-carbon composite refers to a composite containing at least about 5 wt% silicon based on the weight of the silicon-carbon negative electrode active material.

[0073] In some embodiments, the negative electrode active material comprises at least one of artificial graphite, natural graphite, hard carbon, soft carbon, silicon alloy, or silicon oxide.

[0074] When the negative electrode includes a silicon-carbon compound, based on the total weight of the negative electrode active material, silicon:carbon=about 1:10-10:1, and the median particle size Dv of the silicon-carbon compound is 50The negative electrode active material layer may be formed by a method such as evaporation, sputtering, or plating. When the negative electrode includes lithium metal, the negative electrode active material layer may be formed by, for example, a spherical and twisted conductive skeleton and metal particles dispersed in the conductive skeleton. In some embodiments, the spherical and twisted conductive skeleton may have a porosity of about 5% to about 85%. In some embodiments, a protective layer may also be provided on the lithium metal negative electrode active material layer.

[0075] In some embodiments, the negative electrode active material layer may include a binder and optionally a conductive material. The binder improves the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. In some embodiments, the binder includes, but is not limited to: polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.

[0076] In some embodiments, the conductive material includes, but is not limited to: a carbon-based material, a metal-based material, a conductive polymer, or a mixture thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, silver. In some embodiments, the conductive polymer is a polyphenylene derivative.

[0077] In some embodiments, the current collector includes, but is not limited to, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and any combination thereof.

[0078] The negative electrode can be prepared by a preparation method known in the art. For example, the negative electrode can be obtained by mixing an active material, a conductive material, and a binder in a solvent to prepare an active material composition, and coating the active material composition on a current collector. In some embodiments, the solvent may include water, etc., but is not limited thereto.

[0079] Isolation film

[0080] The material and shape of the separator used in the secondary battery of the present application are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed of a material that is stable to the electrolyte of the present application.

[0081] For example, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be selected.

[0082] A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. The inorganic layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate.

[0083] The binder is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene. The polymer layer contains a polymer, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polyvinylidene fluoride and poly(vinylidene fluoride-hexafluoropropylene).

[0084] Electrolyte

[0085] According to some embodiments of the present application, the electrolyte includes an organic solvent, a lithium salt, and optional additives.

[0086] The organic solvent in the electrolyte of the present application may be any organic solvent known in the prior art that can be used as a solvent for the electrolyte. The electrolyte used in the electrolyte according to the present application is not limited, and it can be any electrolyte known in the prior art. The additive of the electrolyte according to the present application may be any additive known in the prior art that can be used as an electrolyte additive.

[0087] In some embodiments, the organic solvent includes, but is not limited to, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), or ethyl propionate (EP).

[0088] In some embodiments, the organic solvent includes an ether solvent, for example, at least one of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME). In some embodiments, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), bistrifluoromethanesulfonyl imide lithium LiN(CF3SO2)2 (LiTFSI), bis(fluorosulfonyl)imide lithium Li(N(SO2F)2)(LiFSI), lithium bis(oxalate borate) LiB(C2O4)2 (LiBOB) or lithium di(oxalate borate) LiBF2(C2O4) (LiDFOB). In some embodiments, the additive includes at least one of fluoroethylene carbonate and adiponitrile.

[0089] According to some embodiments of the present application, the secondary battery of the present application includes, but is not limited to: a lithium ion battery. In some embodiments, the secondary battery includes a lithium ion battery.

[0090] The present application also applies secondary batteries to electronic devices to power loads in the electronic devices. The electronic devices of the present application are not particularly limited. In some embodiments, the electronic devices of the present application include, but are not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.

[0091] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.

[0092] Example 1

[0093] In this embodiment, the positive electrode material is prepared according to the following method:

[0094] (1) Molar ratio (n) Ni :n Co :n Mn=0.60:0.1:0.3) nickel nitrate, cobalt nitrate and manganese nitrate were weighed and added into water to prepare a metal salt solution, wherein the sum of the moles of Ni, Co and Mn in the metal salt solution was nmol, and then, 0.0004 nmol potassium nitrate and 0.012 nmol H2SO4 were added into the mixed solution, and ultrasonic stirring was performed for 2 h to fully mix the mixture to obtain a mixed solution.

[0095] (2) The mixed solution is atomized by ultrasonic wave to form droplets of 18um to 20μm, and then the droplets are added to the roasting furnace for thermal decomposition to prepare the oxide precursor. The temperature of the first temperature zone is 400°C, and the material residence time is 30s; the temperature of the second temperature zone is 1100°C, and the material residence time is 5s; the temperature of the third temperature zone is 700°C, and the material residence time is 3min. The volume concentration of oxygen in the roasting furnace is controlled at 15%. The chemical formula of the positive electrode material oxide precursor is Ni 0.60 Co 0.1 Mn 0.3 K 0.0004 O1. The oxidative precursor is pulverized by air flow to a suitable particle size of D50 of 3.0 μm and Dmax of 15 μm.

[0096] (3) After 1000 g of positive electrode material oxide precursor, 460 g of lithium carbonate and 4 g of zirconium oxide were mixed evenly, the mixture was heated to 930 ° C in an oxygen atmosphere and sintered for 20 h to obtain the positive electrode material LiNi 0.60 Co 0.1 Mn 0.3 K 0.0004 Zr 0.0025 O2.

[0097] Example 2

[0098] The difference between Example 2 and Example 1 is that the amount of H2SO4 added to the solution in step (1) is reduced to 0.0002 nmol. The remaining steps are the same as those in Example 1.

[0099] Example 3

[0100] The difference between Example 3 and Example 1 is that the amount of H2SO4 added to the solution in step (1) is increased to 0.0027 nmol. The remaining steps are the same as those in Example 1.

[0101] Example 4

[0102] The difference between Example 4 and Example 1 is that in step (2), the volume concentration of oxygen is controlled at 21%. The remaining steps are the same as those in Example 1.

[0103] Example 5

[0104] The difference between Example 5 and Example 1 is that in step (1), 0.0002 nmol of calcium nitrate is added to the mixed solution. The remaining steps are the same as those in Example 1.

[0105] Example 6

[0106] The difference between Example 6 and Example 1 is that in step (1), 0.0002 nmol of barium nitrate is added to the mixed solution. The remaining steps are the same as those in Example 1.

[0107] Example 7

[0108] The difference between Example 7 and Example 1 is that in step (1), 0.0002 nmol strontium nitrate is added to the mixed solution. The remaining steps are the same as those in Example 1.

[0109] Example 8

[0110] The difference between Example 8 and Example 1 is that in step (1), a potassium nitrate solution with a ratio of 0.001 nmol is added to the mixed solution. The remaining steps are the same as those of Example 1.

[0111] Example 9

[0112] The difference between Example 9 and Example 1 is that in step (1), a potassium nitrate solution with a ratio of 0.00005 nmol is added to the mixed solution. The remaining steps are the same as those of Example 1.

[0113] Example 10

[0114] The difference between Example 10 and Example 1 is that in step (2), the volume concentration of oxygen is controlled at 12%. The remaining steps are the same as Example 1.

[0115] Embodiment 11

[0116] The difference between Example 11 and Example 1 is that in step (2), the temperature of the third temperature zone is 700° C. and the residence time is 2 min. The remaining steps are the same as those of Example 1.

[0117] Example 12

[0118] The difference from Example 1 is that the amount of H2SO4 added to the solution in step (1) is 0.036 nmol. The remaining steps are the same as those in Example 1.

[0119] Embodiment 13

[0120] The difference between Example 13 and Example 1 is that in step (1), 0.0002 nmol of potassium nitrate and 0.0002 nmol of calcium nitrate are added to the mixed solution. The remaining steps are the same as those of Example 1.

[0121] Embodiment 14

[0122] The difference between Example 14 and Example 1 is that in step (1), 0.0004 nmol of strontium nitrate and 0.0005 nmol of barium nitrate are added to the mixed solution. The remaining steps are the same as those of Example 1.

[0123] Embodiment 15

[0124] The difference between Example 15 and Example 1 is that 1000g of positive electrode material oxide precursor, 460g of lithium carbonate, 4g of zirconium oxide, and 2g of yttrium oxide are mixed evenly, placed in an oxygen atmosphere, heated to 930°C, and sintered for 20h to obtain a positive electrode material LiNi 0.60 Co 0.1 Mn 0.3 K 0.0004 Zr 0.0025 Y 0.0015 O2.

[0125] Example 16

[0126] The difference between Example 16 and Example 1 is that 1000 g of positive electrode material oxide precursor, 460 g of lithium carbonate, and 2.5 g of titanium oxide are mixed evenly, placed in an oxygen atmosphere and heated to 930° C., and sintered for 20 h to obtain a positive electrode material LiNi 0.6 0Co 0.1 Mn 0.3 K 0.0004 Ti 0.0015 O2.

[0127] Embodiment 17

[0128] (1) Nickel nitrate, cobalt nitrate and aluminum nitrate were weighed and added into water in a molar ratio (nNi:nCo:nAl=0.8:0.1:0.1) to prepare a metal salt mixed solution. In the metal salt solution, the sum of the moles of Ni, Co and Al is n mol. Then, 0.0004n mol potassium nitrate and 0.012n mol H2SO4 were added into the mixed solution, and ultrasonic stirring was performed for 2 h to fully mix the mixture to obtain a mixed solution.

[0129] (2) The mixed solution is atomized by ultrasonic wave to form droplets of 18um to 20μm, and then the droplets are added to the roasting furnace for thermal decomposition to prepare the oxide precursor. The temperature of the first temperature zone is 400℃, and the residence time is 30s; the temperature of the second temperature zone is 1100℃, and the material stays in this temperature zone for 5s; the temperature of the third temperature zone is 700℃, and the residence time is 3min. The volume concentration of oxygen in this roasting furnace is controlled at 15%. The chemical formula of the positive electrode material oxide precursor is Ni0.80 Co 0.1 Al 0.1 K 0.0004 O1, the precursor was pulverized by air flow to a suitable particle size of D50 of 2.5 μm and Dmax of 15 μm.

[0130] (3) After 1000 g of positive electrode material oxide precursor, 460 g of lithium carbonate and 2.4 g of zirconium oxide were mixed evenly, the mixture was heated to 830 ° C in an oxygen atmosphere and sintered for 18 h to obtain the positive electrode material LiNi 0.80 Co 0.1 Al 0.1 K 0.0004 Zr 0.0015 O2.

[0131] Embodiment 18

[0132] The difference between Example 18 and Example 1 is that:

[0133] In step (1), nickel chloride, cobalt chloride and manganese chloride are weighed in a molar ratio (nNi:nCo:nMn=0.5:0.2:0.3) and added into water to prepare a metal salt mixed solution.

[0134] Embodiment 19

[0135] The difference between Example 19 and Example 1 is that:

[0136] In step (1), nickel chloride, cobalt chloride and manganese chloride are weighed in a molar ratio (nNi:nCo:nMn=0.7:0.1:0.2) and added to water to prepare a metal salt mixed solution. In the metal salt solution, the sum of the moles of Ni, Co and Mn is nmol. Then, 0.0006n mol of strontium nitrate and 0.018n mol of H2SO4 are added to the mixed solution, and ultrasonic stirring is performed for 2 hours to fully mix and obtain a mixed solution.

[0137] (2) The mixed solution is atomized by ultrasonic wave to form droplets of 18um to 20μm, and then the droplets are added to the calcining furnace for thermal decomposition to prepare the oxide precursor. The temperature of the first temperature zone is 400℃, and the residence time is 30s; the temperature of the second temperature zone is 1100℃, and the material stays in this temperature zone for 5s; the temperature of the third temperature zone is 700℃, and the residence time is 3min. The volume concentration of oxygen in this calcining furnace is controlled at 12%. The chemical formula of the positive electrode material oxide precursor is Ni 0.70 Co 0.1 Mn 0.2 Sr 0.0006 O1, the precursor was pulverized by air flow to a suitable particle size of D50 of 3.2 μm and Dmax of 15 μm.

[0138] (3) After 1000 g of positive electrode material oxide precursor, 460 g of lithium carbonate, and 3.8 g of tungsten oxide were mixed evenly, the mixture was heated to 900 °C in an oxygen atmosphere, and sintered for 16 h to obtain the positive electrode material LiNi 0.70 Co 0.1 Mn 0.2 Sr 0.0006 W 0.002 O2.

[0139] Comparative Example 1

[0140] The difference from Example 1 is that in step (2), the roasting furnace has only two temperature zones, and the material enters the third temperature zone directly from the first temperature. The temperature of the first temperature zone is 400°C, and the material residence time is 30s; the temperature of the third temperature zone is 700°C, and the material residence time is 3min. The remaining steps are the same as Example 1.

[0141] Comparative Example 2

[0142] The difference from Example 1 is that in step (2), the volume concentration of oxygen in the roasting furnace is controlled at 30%. The remaining steps are the same as Example 1.

[0143] Comparative Example 3

[0144] The difference from Example 1 is that in step (1), a potassium nitrate solution with a proportion of 0% is added to the mixed solution. The remaining steps are the same as those in Example 1.

[0145] Comparative Example 4

[0146] (1) Molar ratio (n) Ni :n Co :n Mn =0.60:0.1:0.3) nickel nitrate, cobalt nitrate and manganese nitrate were weighed and added into water to prepare a metal salt solution, wherein the sum of the moles of Ni, Co and Mn in the metal salt solution was nmol, and then 0.0012 nmol of H2SO4 was added into the mixed solution, and ultrasonic stirring was performed for 2 h to fully mix the mixture to obtain a mixed solution.

[0147] (2) The mixed solution is atomized by ultrasonic wave to form droplets of 18um to 20μm, and then enters the roasting furnace for thermal decomposition to prepare the oxide precursor. The temperature of the first temperature zone is 400℃, and the material residence time is 30s; the temperature of the second temperature zone is 1100℃, and the material residence time is 3s; the temperature of the third temperature zone is 700℃, and the material residence time is 3min. The volume concentration of oxygen in the roasting furnace is controlled at 15%. The chemical formula of the positive electrode material precursor is Ni 0.60 Co 0.1 Mn 0.3O1, the precursor is pulverized by air flow to a suitable particle size of D50 of 3.0 μm and Dmax of 15.

[0148] (3) After 1000 g of positive electrode material precursor, 460 g of lithium carbonate, 4 g of zirconium oxide, and 0.13 g of potassium nitrate were mixed evenly, the mixture was heated to 930 ° C in an oxygen atmosphere, and sintered for 20 h to obtain the positive electrode material LiNi 0.60 Co 0.1 Mn 0.3 K 0.0004 Zr 0.0025 O2.

[0149] Comparative Example 5

[0150] The difference from Example 1 is that in step 2, the pyrolysis temperature in the third temperature zone is 600° C. and the residence time is 1 min.

[0151] Test Method

[0152] Free SO4 2- Test: Weigh 0.5 g of sample and dissolve it in 50 ml of water. After filtration under ultrasonic for 5 minutes, measure the free SO4 in the filtrate using ion chromatography (instrument: Thermo Fisher ion chromatograph ICS6000 HPIC). 2- The molar content of the ion is a2.

[0153] Since the molar content of sulfur in sulfate ions is 1 / 3, the molar content of sulfur in the free sulfate ions of the positive electrode material is A2=a2 / 3.

[0154] Test for the total molar content of M and S elements: Take 0.3 g of sample and add aqua regia for digestion. After cooling and constant volume, the total mass content of M and S elements is tested by Agilent 5110ICP-OES. The molar content of M and S elements is obtained by converting the total mass content of M and S elements, where the total molar content of S element is A2 (unit: ppm).

[0155] The surface enrichment of sulfur element α = A2 / A1. The ratio of A1 to A2 can characterize the enrichment of sulfur element on the surface of the positive electrode material. The larger the ratio of A1 to A2, the higher the sulfur content on the surface of the positive electrode material, and the sulfur element is enriched on the surface of the positive electrode material; the smaller the ratio of A1 to A2, the lower the sulfur content on the surface of the positive electrode material, and the higher the sulfur element in the bulk phase.

[0156] The test method for the concentration distribution of M element is as follows:

[0157] The test method for the average concentration X1 of the element M in the center area and the average concentration X2 in the surface area of ​​the positive electrode material particles is as follows: use a Hitachi ion cutting instrument to prepare a cross-section sample, use a Hitachi S4800 scanning electron microscope to select a suitable cross-section field of view, and then use EDS to perform line scanning or point scanning on the particle cross section within the 5k field of view. For example, the point scanning method can be used to measure the mass content of the element M at 10 positions (generally at least 5 points) in the center area of ​​the particle cross section, and the mass content of the element M is summed and averaged to obtain X1; measure the mass content of the element M at 10 positions in the surface area of ​​the particle cross section, and the mass content of the element M is summed and averaged to obtain X2. Figure 3 As shown in the particle cross-sectional view, the radius of the particle is L, the area from the center of the particle to the distance L / 2 from the center of the particle is the central area, and the area from the position L / 2 of the particle to the surface of the particle is the surface area. When the positive electrode material contains two or more elements M, X1 and X2 of each element M are measured separately, and the X2 / X1 value of the corresponding element is calculated accordingly.

[0158] For point scanning and line scanning, combined Figure 3 The instructions are as follows:

[0159] Scan: In the center area ( Figure 3 5-10 points are selected for EDS measurement (inside the dotted circle shown in the figure), and the average value is taken to obtain the X1 value; in the surface area ( Figure 3 Select 5-10 points (outside the dotted circle shown) for EDS measurement and take the average value after measurement to get the X2 value.

[0160] Line scan: In the central area (i.e. Figure 3 At least three line positions are randomly selected for line scanning (inside the dotted circle shown in the figure), and the average value is taken after measurement to obtain the X1 value; the surface area (i.e. Figure 3 At least three line positions are randomly selected for line scanning (outside the dotted circle shown in the figure), and the average value is taken after measurement to obtain the X2 value. In actual testing, point scanning and line scanning can also be used in combination.

[0161] The test method for the structural recovery degree δ is as follows:

[0162] Electrochemical in situ XRD was used with Bruker D8 Advance (Cu target) and BlueDian (5mA, 5V) equipment to test the structural changes during the charge and discharge process. The charge and discharge voltage range was 2.8V-4.35V. The XRD spectrum was then fitted with Jade software to obtain the diffraction angles corresponding to the (003) peaks at the beginning and end of charge and discharge.

[0163] The particle size is determined by using a Malvern 3000 laser particle size analyzer to measure and obtain the average particle size of the volume or number distribution of the cathode material precursor or the ternary cathode material.

[0164] The test method for the specific surface area of ​​the positive electrode material is: using Tristar3020 for testing, as follows: weigh the mass of the empty sample tube m1; take 3g of sample and add it to the sample tube through a long-necked funnel; vacuum degas for 1h at 300℃, and weigh the mass of the sample tube m2 after cooling; the sample mass m=m2-m1. The sample tube is placed in liquid nitrogen, and the nitrogen adsorption amount V of the sample is measured at a series of relative pressures P / P0 to obtain the adsorption isotherm. Among them, P / P0 is set to 0.05 / 0.1 / 0.15 / 0.20 / 0.25 / 0.30. Fit the isothermal adsorption curve, calculate the monolayer saturated adsorption amount Vm according to the slope and intercept; then calculate the specific surface area according to Vm.

[0165] Test method for the volume percentage of positive electrode material particles with a particle size of less than 1 μm: Test the volume percentage of positive electrode material particles below 1 μm: Weigh 1 g of sample and put it into the mold of a compaction density meter (American carver 4350) and press it with a pressure of 6 T for 30 seconds, then take out the sample and use Malvern 3000 laser particle size analyzer to test the volume percentage of particles below 1 micron.

[0166] Test method for average particle size of primary particles:

[0167] The cross-section samples of the positive electrode materials were prepared using an ion cutting instrument, and then the cross-section morphology was tested using a Hitachi S4800 scanning electron microscope, and 10 photos were taken at a magnification of 5K. All the pictures were imported into the software NanoMeasure to count the size of the particles.

[0168] Electrochemical performance test:

[0169] The electrochemical performance of the material was evaluated using a button-type half-cell, and the positive electrode materials prepared in the above examples and comparative examples were assembled to form button-type batteries. The specific method is as follows: the positive electrode material, conductive carbon black, and PVDF were weighed in a mass ratio of 93:5:2, N-methyl-2-pyrrolidone (NMP) was added at a solid content of 50%, and a high-speed disperser was used to adjust the viscous slurry, which was evenly coated on an aluminum foil with a scraper, and after being dried in an oven at 80°C, it was rolled and cut into a positive electrode sheet with a diameter of 14 mm. A 16 mm lithium sheet was used as the negative electrode sheet, a Celgard polypropylene film was used as the diaphragm, and a carbonate solution of LiPF6 with a concentration of 1 mol / L was used as the electrolyte. The assembly was performed in a glove box filled with argon to obtain a button-type half-cell.

[0170] After the assembled button half-cell was left to stand for 12 hours, the capacity and cycle performance were tested at 25°C and 3.0-4.45V using the LAND battery test system, with the nominal capacity 1C set to 200mAh / g. After 50 cycles of 0.5C charge and 1C discharge, the ratio of the 50th week discharge capacity to the first week discharge capacity is the 50-week cycle retention rate.

[0171] Test method for DC internal resistance of positive electrode material:

[0172] The capacity and cycle performance tests were performed using the LAND battery test system at 25°C and 3.0V to 4.4V, with the nominal capacity 1C set to 200mAh / g. In addition, the voltage U at the initial time of each weekly discharge was recorded. A And the voltage data U at 60s B , discharge current I Dis The calculation formula of DC internal resistance is DCR = (U A -U B ) / I Dis .

[0173] Table 1

[0174]

[0175] Table 2

[0176]

[0177]

[0178] From the above Tables 1 and 2, compared with Comparative Examples 1-5, in the positive electrode material prepared in Example 1-19, the concentration of element M in the surface area is X1, the concentration of element M in the central area is X2, X1, X2 satisfy 1.2≤X2 / X1≤20, the total mass content of sulfur in the positive electrode material is A1, the mass content of sulfur in the free sulfate in the positive electrode material is A2, A1 and A2 satisfy (A2 / A1)%≤70%, and the test results show that the element M and the sulfur element satisfy the above relationship. The positive electrode material has good specific capacity and also has good cycle performance and lower DC internal resistance. After a large number of experiments, the inventor speculates that it may be due to the high content of element M near the surface area of ​​the particle, and the M element increases the unit cell volume of the surface area of ​​the particle, while the content of element M near the central area of ​​the particle is small, so that the unit cell volume at the central area of ​​the particle is relatively small, thereby forming a compressive stress of the particle from the surface area toward the central area, and the compressive stress can inhibit the lattice expansion during the charge and discharge process, improve the stability of the particle, and thus improve the gas production performance and long-term cycle performance. At the same time, when the ratio of A2 to A1 is ≤70%, it indicates that part of the sulfur atoms are doped into the lattice of the positive electrode material. Appropriate amount of sulfur atom doping can increase the migration rate of lithium ions, inhibit heterogeneous reactions, reduce the lattice rotation of the positive electrode material, and improve the rate and structural stability of the positive electrode material.

[0179] Compared with Example 1, the second temperature zone is cancelled in Comparative Example 1, and the (A2 / A1)% in the positive electrode material is characterized to be 90%, indicating that the S element in the positive electrode material is enriched in the positive electrode material, and the amount of S element doping in the bulk phase of the positive electrode material is small, which makes it difficult to suppress the lattice deformation during the charge and discharge process, resulting in a decrease in the cycle stability of the positive electrode material in Comparative Example 1 and an increase in the DC internal resistance.

[0180] Compared with Example 1, in Comparative Example 2, the oxygen volume concentration in the roasting furnace is controlled to be 30%, which is a higher oxygen concentration. 2- It is difficult to decompose to form S 2- The (A2 / A1)% of the positive electrode material obtained by characterization is 73%, indicating that the S element in the positive electrode material is enriched in the positive electrode material, indicating that the amount of S element doping in the bulk phase of the positive electrode material is small, and it is difficult to inhibit the lattice deformation during the charge and discharge process, resulting in a decrease in the cycle stability of the positive electrode material in Comparative Example 2 and an increase in the DC internal resistance.

[0181] Compared with Example 1, no K element is added in step (1) of Comparative Example 3, and the positive electrode material obtained by characterization does not have a distribution difference of the M element in the surface area and the inner area, and the crystal structure cannot form compressive stress, resulting in a decrease in the cycle stability of the positive electrode material in Comparative Example 3 and an increase in the DC internal resistance.

[0182] Compared with Example 1, in Comparative Example 4, the K element was not added in step (1), and the K element was added in step (3) for solid phase doping. It was characterized that the distribution difference of the K element in the surface area and the inner area of ​​the positive electrode material was small, and the crystal structure could not form compressive stress, resulting in a decrease in the cycle stability of the positive electrode material in Comparative Example 3 and an increase in the DC internal resistance.

[0183] Compared with Example 1, in Comparative Example 5, the temperature and material residence time of the third temperature zone in step (2) are reduced, and the concentration ratio of the K element in the surface area and the central area in the obtained positive electrode material is characterized to be 23. Excessive element M is enriched in the surface area of ​​the particles and will occupy the lattice lithium site, resulting in a decrease in the cycle stability of the positive electrode material in Comparative Example 5 and an increase in the DC internal resistance.

[0184] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A positive electrode material, characterized in that: The positive electrode material comprises an element M, wherein the element M is selected from at least one of Na, K, Mg, Ca, Sr and Ba; the positive electrode material comprises a plurality of particles, the cross section of the particles comprises a central region and a surface region, and the cross section of the particles is tested by an energy spectrometer, and the average concentration of the element M in the central region is X1, and the average concentration of the element M in the surface region is X2, and X1 and X2 satisfy: 1.2≤X2 / X1≤20; the total molar content of sulfur in the positive electrode material is A1, and the molar content of sulfur in the free sulfate ions in the positive electrode material is A2, and (A2 / A1)%≤70%.

2. The positive electrode material according to claim 1, characterized in that 30%≤(A2 / A1)%≤50%.

3. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following conditions: (1) Based on the total molar amount of the positive electrode material, the molar content of the element M is 50 ppm to 1000 ppm; (2) Based on the total molar amount of the positive electrode material, the molar content of the element S is 100 ppm to 3000 ppm.

4. The positive electrode material according to claim 1, characterized in that The positive electrode material is a single crystal material, the particles include primary particles, and the average particle size of the primary particles is 1 μm to 5 μm.

5. The positive electrode material according to claim 1, characterized in that In the first cycle of charge and discharge of the positive electrode material, the structural recovery degree δ of the positive electrode material satisfies: 99.70%≤δ≤100.00%, wherein δ=θ1 / θ2*100%, θ1 is the diffraction angle of the X-ray diffraction (003) peak of the positive electrode material at the beginning of the first cycle of charging, and θ2 is the diffraction angle of the X-ray diffraction (003) peak of the positive electrode material at the end of the first cycle of discharge.

6. The positive electrode material according to any one of claims 1 to 5, characterized in that The general formula of the positive electrode material is: Li x Ni a Co b Q c M d O2, wherein 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.35, a+b+c=1, 0.00005<d≤0.001, and the Q element includes at least one of Mn and Al.

7. The positive electrode material according to any one of claims 1 to 5, characterized in that The positive electrode material further contains element N, which is selected from one or more of Zr, Ti, Al, W, Ce or Y. Based on the total molar amount of the positive electrode material, the molar content of the element N is e, 0<e≤0.

05.

8. The positive electrode material according to any one of claims 1 to 5, characterized in that The positive electrode material satisfies at least one of the following conditions: (1) The volume distribution particle size D50 of the positive electrode material is 2.5 μm to 5.0 μm; (2) The specific surface area of ​​the positive electrode material is 0.5 m 2 / g to 1.2m 2 / g; (3) When the positive electrode material is subjected to a pressure of 6 t, the volume proportion of particles with a particle size of less than 1 μm is less than 4%.

9. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, characterized in that: The positive electrode active material layer includes the positive electrode material according to any one of claims 1 to 8.

10. A secondary battery, comprising a housing, an electrode assembly, and an electrolyte or an electrolyte, wherein the electrode assembly and the electrolyte or the electrolyte are both located in the housing, and the electrode assembly comprises a separator and a negative electrode sheet, characterized in that: The electrode assembly further comprises the positive electrode sheet as claimed in claim 9, and the separator is disposed between the positive electrode sheet and the negative electrode sheet.

Citation Information

Cited By

  • Positive electrode material, positive electrode sheet and secondary battery

    WO2026138645A1